Relationships and tensions between the curricular program and the lived curriculum. A narrative research. - Martín-Alonso, Diego; Sierra-Nieto, José Eduardo; Blanco-García, Nieves (Elsevier, 2021)
This research focused on the relationships that teachers and students establish with curricular programs, the tensions they experience, and the effects this has on shaping the classroom experience. The study employed a narrative research approach using observation and conversational interviews, with fieldwork conducted over two school years with two teachers. It was found that (1) the teaching profession juggles between the two curricular worlds (the curricular program and the lived curriculum), (2) inherent educational practice tensions were generated, and (3) methods needed to be identified to harness these tensions fruitfully to avoid conflict.
Keywords: Educación - Investigación; Relación educativa; Currículum; Experiencia vivida